Management of strangulated inguinal hernia with resection and anastomosis in a primary health care setting during COVID-19 crisis - Sapkota, Sanju; Dangal, Binod; Diwakar, Uday Pratap; Khadka, Himshail (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Longstanding reducible hernia should be intervened timely so as to prevent the risk of strangulated hernia and resection and anastomosis of gut. Strangulated hernia is a surgical emergency and only timely surgical intervention can prevent from further deterioration of patient’s health condition. Case Report: There was a case of 75 years male from rural area of Eastern Nepal at Charikot Hospital emergency department, with the complaint of severe pain and swelling over right inguinal region, associated with abdominal distension, vomiting, not passing stool for 3 days. He had history of swelling of right inguinoscrotal region for last 5 years. Intraoperative finding showed that there was indirect hernia and the content was jejunum and omentum which was gangrenous, resection and anastomosis along with bassini’s repair was done. Conclusion: Hernia should be managed as soon as the diagnosis is confirmed before emergency visit due to serious risk of obstruction and strangulation. So, we should repair any inguinal hernia on an elective basis in any age group.